Mercado internacional de energías renovables: producción y exportación de biodiesel en Michoacán - Aburto Martínez, Jannete Andrea (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
To international scale the climate change and the depletion of the reservations of fossil fuels; they have provoked the need to resort to sources of renewable energy as the biofuels: ethanol and biodiesel. The previous thing projects a long-term trend for the substitution of fossil fuels for renewable energies. In this respect the countries that join to this restructuring, have the possibility of acceding to economic opportunities of considerable magnitudes due to the growth of the use of energy. Mexico possesses the endowment of natural and human resources to accede to this type of opportunities on the markets of renewable energies. Especially for the production and export of biofuels by means of the utilization of his comparative and competitive advantages, in fulfillment with the criteria for a sustainable development. In the present investigation two aims appear, a) to determine the viability of the production of biofuels in the international area from the employment of agricultural inputs linked to the supply; as well as b) to demonstrate the viability for the production and export of biodiesel in coast and warm land in Michoacan from the utilization of his comparative and competitive advantages. Analyses determined the existence of a relation of long term between the international prices of the petrol and the principal agricultural inputs used in the production of ethanol (i.e. maize, sugar cane). For the second aim of investigation, the hypothesis affirmed that the comparative and competitive advantages in the coast and warm land contribute in order that the production and export of biodiesel is viable in Michoacan, which was demonstrated by means of an index of competitiveness, an analysis of cost-benefit and a econometric model of panel-data

A escala internacional el cambio climático y el agotamiento de las reservas de combustibles fósiles, han provocado la necesidad de recurrir a fuentes de energía renovable como los biocombustibles: etanol y biodiesel. Lo anterior proyecta una tendencia a largo plazo para la sustitución de combustibles fósiles por energías renovables. En este sentido los países que se incorporen a esta reconversión, tienen la posibilidad de acceder a oportunidades económicas de magnitudes considerables debido al crecimiento del uso de energía. México cuenta con la dotación de recursos naturales y humanos para acceder a este tipo de oportunidades en los mercados de energías renovables. En particular para la producción y exportación de biocombustibles mediante el aprovechamiento de sus ventajas comparativas y competitivas, en cumplimiento con los criterios para un desarrollo sustentable. En la presente investigación se plantean dos objetivos, a) determinar la viabilidad en el ámbito internacional para la producción de biocombustibles a partir del empleo de insumos agrícolas vinculados a la alimentación; así como b) demostrar la viabilidad para la producción y exportación de biodiesel en las Regiones de Costa y Tierra Caliente en Michoacán a partir del aprovechamiento de sus ventajas comparativas y competitivas. En el primer caso la hipótesis de investigación se planteó que la producción de biocombustibles en el ámbito internacional no es viable a partir del empleo de insumos agrícolas vinculados a la alimentación, situación que se comprobó mediante los modelos econométricos de cointegración y corrección de errores. Dichos análisis determinaron la existencia de una relación de largo plazo entre los precios internacionales de la gasolina y los principales insumos agrícolas utilizados en la producción de etanol (i.e. maíz, caña de azúcar).
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2010-0012; Biocombustibles; Desarrollo sustentable; Países de la OCDE; TLCUE; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/946